Building Pillars of Justice and Order: Uncovering the Challenges and Solutions of Equitable Law Enforcement in Indonesia - Dessani, Yulia; Afrilia, Bella; Nelwati, Sasmi (Yayasan Lembaga Studi Makwa, 2023)
Enforcing fair and effective law in Indonesia is a complex challenge that requires a holistic approach from various stakeholders. Law enforcement institutions such as the judiciary, prosecution, police, and other legal bodies play a crucial role in upholding justice and maintaining societal order. One critical aspect in this context is ensuring the judiciary's independence from political pressure or other external influences, so that decisions are based on objective and fair legal principles. Legal reform is urgently needed to enhance transparency in legal processes, strengthen accountability, and uphold professionalism through continuous education and training of legal professionals. Strengthening active participation of the public in monitoring law enforcement agencies is also crucial to build public trust and maintain the integrity of the legal system as a whole. Developing an inclusive and comprehensive legal system should be a priority in addressing various legal challenges from local to national levels. By implementing these steps, Indonesia can strengthen the foundation for sustainable rule of law, which in turn will enhance justice for all citizens and create an environment conducive to sustainable and stable development. These efforts encompass not only structural and operational improvements in legal institutions, but also support the realization of a legally educated society aware of its rights, thus addressing social and economic challenges consistently and fairly. In-depth research on the implementation of legal policies is also necessary to identify areas needing improvement and evaluate the effectiveness of measures taken to achieve these goals.